Hormonal regulation of the regular and 'off season' floral induction process of longan (Dimocarpus longan) trees - K. F. Bangerth (2018)
Regulatory mechanisms of floral induction (FI) in angiosperm fruit trees in comparison to annual plants will be described. Floral induction in trees is a quantitative process whereas in monocarpic annual plants it is a qualitative one. The decision whether a shoot apical bud (SAB) in trees is transformed into a floral bud or stays vegetative is regulated by a great number of environmental and endogenous factors which are presumably mediated by correlative hormonal signals into the morphogenetic process of FI. In our experiments we investigated the hormonal changes that occur during the process of FI in SABs, leaves, and the tissue beneath the SAB, using longan trees as a model system. Longans require low temperatures (≤ 15 to 18°C), sufficient light, and mature leaves for FI. However, the low temperature requirement can be substituted by the application of potassium chlorate (KClO3), which allows 'off season' FI year round. We used these possibilities in field and greenhouse experiments to investigate the hormonal (auxin, gibberellins, abscisic acid, cytokinins, and ethylene) changes which occur during low temperature and KClO3induced FI and the inhibition of this process by defoliation and shading the shoots/trees. Results of several years experiments revealed that obviously cytokinins and here particularly zeatin/zeatin riboside, play a paramount role in the FI process of longans. Auxins and gibberellins may have an opposite, antagonistic effect to cytokinins on FI but our presently available data are not as clear as those with cytokinins. However, this may be related to the fact that only a limited number of gibberellins have been analyzed and for IAA the possibly more important polar auxin transport was measured only in leaf exudates and only once in the shoot.